Teacher Competence Surah An Nahl Verse 90 - Arsalan, Muammar Zuhdi (ALACRITY : Journal of Education, 2024)
The background for writing this journal is because of the importance of the competencies that a teacher must have. The competence of a teacher greatly determines the quality of students. It is hoped that later this will be able to increase the insight of writers and readers about teacher competence, and of course also be able to apply the verses of the Koran in everyday life. This research is qualitative research with data obtained through literary sources (library research), namely literature review through library research. The primary data source for this research is Tafsir books, then other related sources. The results of this research show that in Q.S. an-Nahl [16]: 90 Social Competence and professional competence. Social competence takes the form of: Acting fairly towards multicultural students, being kind towards students, helping to lighten the burden on students, prohibiting students from doing things that are not good, and educating students to achieve mental cleanliness. Professional Competency consists of being a human learner.